AKTYWNOŚĆ STUDENTÓW I ICH WNIKLIWOŚĆ NA HOSPITACJACH LEKCJI PRÓBNYCH - Skulimowska, Agnieszka (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
After a pedagogical experiment the author compares the activity of primary teaching students, during experimental lessons and while discussing them afterwards, lessons taught in traditional ways and those recorded and watched on video. The students' insight during the experimental and traditional classes was also discussed.
Keywords: aktywność; hospitacje; eksperyment pedagogiczny; telehospitacje; activity; experimental lessons; pedagogical experiment; Tv-experimental lessons; Neodidagmata